Tingkat Kepuasan Remaja Surabaya terhadap Program Pagi Kanca Muda di Radio EBS FM Surabaya - Elma Gloria Pasaribu (Jurnal Spektrum Komunikasi, 2018)
This study was conduct to examine how the level of satisfaction of Surabaya teenagers against program “Pagi Kanca Muda” on Radio EBS FM Surabaya. To find out how the level of satisfaction of Surabaya teenagers against program “Pagi Kanca Muda” on Radio EBS FM Surabaya, researcher is using Uses and Gratification Thory, the type of this study is descriptive quantitative research, the technique of collecting data in this study is using survey methods. From the data collected is analyzed in a descriptive to describe the satisfaction of Surabaya teenagers against program "Pagi Kanca Muda" on Radio EBS FM Surabaya. There are 4 categories to determine the level of satisfaction of Surabaya teenagers, specifically the satisfaction of personally identifying, satisfaction of information, satisfaction of integration and social interaction, and satisfaction of diversion. Satisfaction is measured by looking at the discrepancy between the expected satisfaction (Gratification Sought) and the satisfaction obtained (Gratification Obtained). By looking at the ratio of gratification motive scores obtained with the needs of listeners by listening to the progam "Pagi Kanca Muda” on Radio EBS FM Surabaya, the result mean value calculation Gratification Sought (50,89) is smaller than the value of Gratification Obtained (66,16 ) (needs GS < GO). Which means that satisfaction has arisen in Surabaya teenagers against program " Pagi Kanca Muda" on Radio EBS FM Surabaya. Additionally the difference between expectations and satisfaction of Surabaya teenagers against program "Pagi Kanca Muda" on Radio EBS FM Surabaya is significant and can be used on all existing listeners. Keywords : Level of Satisfaction, Surabaya Teenagers, Program "Pagi Kanca Muda"